Analysis of the Strategy in Developing the Potential of Child-Friendly Tourism in Medan City - Badriyah, Badriyah; Sismudjito, Sismudjito; Humaizi, Humaizi (Dinasti International Journal of Economics, Finance & Accounting, 2023)
The purpose of this research was to analyze the tourism strategies in order to Developing the potential of Child-Friendly Tourism at Belawan Bahari Village, Medan Belawan District in Medan City. This research applied descriptive qualitative approach as its method. Sources of data are obtained from informants through interviews and focus group discussions, observation as well as documentation. The analysis of Data are divided into four stages, namely data collection, data reduction, data presentation and drawing conclusions. This research results have been found that the development of child-friendly tourism at Belawan Bahari Village, Medan Belawan District, Medan City has tourism potential that get further developed in the form of marine tourism, seafood culinary tourism and its cultural so it can be conclude that this area are worth to developed as child-friendly tourist destination or place. The potential of tourism at Belawan Bahari Village is seems very prospective to continue to be developed in the nearest future, especially for its natural and culinary tourism which own its uniqueness for tourists. The Provision of infrastructure facilities which is available even though still in minimal conditions which requires support and attention from the government and those are private sector companies as well as participation from its community. Supporting facilities such as short distance to access, the existence of adequate public transportation and also the enthusiasm of the local community who really hope that the stereotypes relates to Belawan Bahari Village about being slum village are change into a child-friendly coastal village which become the role model for developing sustainable of coastal tourism that is Child friendly.